HypoglycAemic, Phytochemical and other Properties of Allium cepa L. - Sirag, Nazar; Ahmed, EL-Hadi M.M; EL -Subaki, Hassan (مجلة الجزيرة للعلوم الصحية; مجلد 3 عدد 2 (2007), 2007)
In the view of the promising potential of hypoglycaemic plants, 19 plants indigenous to Sudan and of common use in Sudanese folk-medicine, were screened for their hypoglycaemic activity. Out of these Allium cepa L being the most active, safe and non toxic, available and affordable, hence it had been selected for further investigation. Allium cepa was subjected to chemical tests and chromatographic procedures for the detection of its active components present.  Conducted tests and procedures confirmed the presence of sulfur compounds.  Comparative chromatographic methods as thin layer chromatography and C–18 high performance liquid chromatography revealed that the aminoacid, cysteine (0.059%) occurs as a major  constituent found in Allium cepa.   Allium cepa alcoholic extract was found to possess its hypoglycemic effect (36.33 mg/dl – reduction of glycemia) through a synergestic action of its similar sulfur phytoconstituents present, since less activity was exhibited by each of it’s fractions (aqueous and organic) obtained when partioned with hexane. We can conclude that the integrated properties of the active medicinal products especially edible plants with their hypoglycaemic activity, make their use for the control and prevention of diabetes mellitus possible and recommendable.  Unstability, similarity in constituents and synergy of their activity give reasons for not to isolate individual compounds from onions and give credits to use them whole as a crude drug or a concentrated extract.  Furthermore, descriptive characters, chemical tests and chromatographic profiles obtained in this study could be used as measures to standardize red onion growing in Sudan.